1997
DOI: 10.1017/s0890037x00043190
|View full text |Cite
|
Sign up to set email alerts
|

Control of Volunteer Sethoxydim-Resistant Corn (Zea mays) in Soybean (Glycine max)

Abstract: Research was conducted in 1995 and 1996 to determine the potential for commonly used volunteer corn herbicides to control volunteer sethoxydim-resistant (SR) corn in soybean. Greenhouse studies showed that the SR corn hybrid tolerated 181 times more sethoxydim than the susceptible sister hybrid. SR corn also tolerated other acetyl CoA carboxylase (ACCase) inhibitors including fluazifop-P, quizalofop-P, and clethodim with 30 X, 27 X, and 7 × magnitudes of tolerance, respectively, compared with the susceptible h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 8 publications
2
20
0
8
Order By: Relevance
“…In this study, PRE or POST application of imidazolinones resulted in poor control of volunteer corn. In contrast, Young and Hart (1997) reported 70 and 83% control of volunteer corn with imazaquin and imazethapyr plus imazaquin in soybean. More research is required to identify a PRE herbicide with excellent efficacy for volunteer corn control, soybean selectivity as well as to better understand the natural range in tolerance of volunteer corn lines to herbicides.…”
Section: Post Herbicide Studymentioning
confidence: 89%
See 1 more Smart Citation
“…In this study, PRE or POST application of imidazolinones resulted in poor control of volunteer corn. In contrast, Young and Hart (1997) reported 70 and 83% control of volunteer corn with imazaquin and imazethapyr plus imazaquin in soybean. More research is required to identify a PRE herbicide with excellent efficacy for volunteer corn control, soybean selectivity as well as to better understand the natural range in tolerance of volunteer corn lines to herbicides.…”
Section: Post Herbicide Studymentioning
confidence: 89%
“…For example, reported > 90% control of volunteer corn with diclofop. Young and Hart (1997) reported > 90% control with sethoxydim or quizalofop. Deen et al (2006) reported that use of a recommended adjuvant significantly improved the effectiveness of ACCase inhibitors, specifically when reduced rates were applied.…”
Section: Post Herbicide Studymentioning
confidence: 99%
“…The possibility for yield reduction, interference with harvest, poorer soybean seed quality, and general unattractiveness in a soybean crop qualify volunteer corn as a weed (Andersen 1976;Young and Hart 1997). Volunteer corn has been proven to reduce soybean yields because of interspecific competition (Andersen et al 1982;Beckett and Stoller 1988;Zimdahl 2004).…”
mentioning
confidence: 99%
“…Many ACCase graminicides effectively control volunteer corn, including diclofop (Andersen 1976;Andersen et al 1982), sethoxydim, quizalofop (Young and Hart 1997), fluazifop (Beckett and Stoller 1988), clethodim, and fenoxaprop (Deen et al 2006). One of the difficulties in convincing producers to incorporate these herbicides in soybean production is that at current prices, the addition of these herbicides double or triple herbicide costs compared with glyphosate alone (Johnson et al 2015).…”
mentioning
confidence: 99%
“…Controlling volunteer corn in soybean has been a challenge both prior to, and after the introduction of HR hybrid corn, yet multiple chemical options are available with adequate efficacy, including clethodim, diclofop, quizalofop-p-ethyl, fenoxaprop-p-ethyl, sethoxydim, and fluazifop-p-ethyl [5,[20][21][22][23] to control glyphosate-resistant (GR) volunteer corn in soybean [22]. Control of volunteer corn was dose dependent, with the lowest doses of clethodim, fenoxaprop-p-ethyl, and fluazifop-p-butyl resulting in inadequate control of volunteer corn (less than 80% control on a 0%-100% control scale).…”
Section: Control Options For Volunteer Cornmentioning
confidence: 99%